2011
DOI: 10.1063/1.3625604
|View full text |Cite
|
Sign up to set email alerts
|

Microbridge structures for uniform interval control of flowing droplets in microfluidic networks

Abstract: Precise temporal control of microfluidic droplets such as synchronization and combinatorial pairing of droplets is required to achieve a variety range of chemical and biochemical reactions inside microfluidic networks. Here, we present a facile and robust microfluidic platform enabling uniform interval control of flowing droplets for the precise temporal synchronization and pairing of picoliter droplets with a reagent. By incorporating microbridge structures interconnecting the dropletcarrying channel and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Thus, the intrinsic problem of cell attachment, which leads to cell loss, could not be solved. The reduction in the number of attached cells that resulted from the use of the proposed injection method is critical for determining the efficiency of single‐cell encapsulation into droplets .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the intrinsic problem of cell attachment, which leads to cell loss, could not be solved. The reduction in the number of attached cells that resulted from the use of the proposed injection method is critical for determining the efficiency of single‐cell encapsulation into droplets .…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2014) reported a microfluidic system that can handle multiple solutions even with a single syringe pump, and applied this system to the external-gelationbased production of alginate microparticles. Lee et al (2011) used a microchannel system that can additionally introduce a flow of calcified oleic acid to the droplet flow in an oil phase, and used this system to produce alginate microparticles. The authors further proposed a technique to effectively remove the continuous phase of oil by using a hydrophobic filter paper .…”
Section: Droplet Micro Uidics To Produce Alginate Particlesmentioning
confidence: 99%
“…In combination with the guidance of microfluidic or micropatterning technologies, the geometry of the hydrogel constructs can be precisely controlled at the cellular scale. To date, a variety of shapes of hydrogels, including particles, [7][8][9] fibers, [10][11][12] and sheets, [13][14][15] have been used as building units in bottom-up approaches to the fabrication of macro-scale multi-cellular architectures.…”
Section: Introductionmentioning
confidence: 99%